2019
DOI: 10.1021/acs.macromol.8b01917
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Nanoparticles in Entangled Poly(vinyl alcohol) Solutions and Gels

Abstract: We studied the diffusion of gold nanoparticles within entangled solutions and gels formed by high molecular weight (M w = 89000 g/mol) poly­(vinyl alcohol) (PVA) in water by using fluctuation correlation spectroscopy (FCS). The nanoparticle size (2R) was varied between 5 and 30 nm, and the PVA volume fraction (ϕ) was chosen to be in the entangled regime. We found that existing hydrodynamic and obstruction models are inadequate to describe the size dependence of the particle diffusion coefficient (D). For size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…48−53 Parrish et al 52 showed that the network confinement and heterogeneity would suppress the NP diffusion when the NP size is comparable to the gel mesh size. Senanayake et al 53 found that the presence of physical cross-linking in addition to entanglements would sharply slow down the NP mobility, which can be explained qualitatively by recently developed force-based nonlinear Langevin theory. 34 However, by experiments, polymer network quality is hard to be precisely controlled.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…48−53 Parrish et al 52 showed that the network confinement and heterogeneity would suppress the NP diffusion when the NP size is comparable to the gel mesh size. Senanayake et al 53 found that the presence of physical cross-linking in addition to entanglements would sharply slow down the NP mobility, which can be explained qualitatively by recently developed force-based nonlinear Langevin theory. 34 However, by experiments, polymer network quality is hard to be precisely controlled.…”
Section: Introductionmentioning
confidence: 97%
“…Though the network confinement effect has been fully considered in these theories, the impact of the permanent cross-links on the network dynamics and thereby the coupled NP mobility is missing. By use of dynamic light scattering, X-ray photon correlation spectroscopy, fluctuation correlation spectroscopy, or single particle tracking, the particle dynamics in polymer gels, consisting of either chemically or physically cross-linked networks of polymer chains immersed in solvent, has been investigated experimentally. Parrish et al showed that the network confinement and heterogeneity would suppress the NP diffusion when the NP size is comparable to the gel mesh size. Senanayake et al found that the presence of physical cross-linking in addition to entanglements would sharply slow down the NP mobility, which can be explained qualitatively by recently developed force-based nonlinear Langevin theory .…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43][44] Not only do ligands impact NP surface chemistry, but they add an additional level of complexity to the diffusive behavior of the particles by changing the hydrodynamic diameter and introducing ligand-matrix effects. The effect of grafted polymer chains on NP surfaces has received substantial attention in the context of polymer melts and solutions, 35,[45][46][47][48][49][50][51] but these systems have important differences from networks and gels.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior investigations have looked at nanoparticle diffusion in polymer networks using spherical or rodlike penetrants with well-defined geometry. Choi et al found that nanorods can exhibit diffusion coefficients orders of magnitude larger than predicted by continuum models because their anisotropic shape allows unhindered diffusion along the long axis through the network mesh . Cai et al have proposed a hopping diffusion mechanism for spherical nanoparticles in polymer networks, where the network cage conformation must extend to allow the nanoparticle to hop through .…”
Section: Introductionmentioning
confidence: 99%